Social Networks in Natural Resource Management: What Is There to Learn from a Structural Perspective? - Örjan Bodin; Beatrice Crona; Henrik Ernstson (Ecology and Society, 2006)
Social networks among actors and stakeholders are gaining attention in studies of natural resource management, particularly those of adaptive management based on different forms of participation and co-management. In this sense, social networks have primarily been envisioned as enabling different actors to collaborate and coordinate management efforts. Here, we continue the discussion initiated by Newman and Dale (2005), which highlighted the fact that not all social networks are created equal. We discuss the relation between some structural characteristics and functions of social networks with respect to natural resource management, thus focusing on structural implications that are often overlooked when studying social networks within the context of natural resource management. We present several network measures used to quantify structural characteristics of social networks and link them to a number of features such as learning, leadership, and trust, which are identified as important in natural resource management. We show schematically that there may be inherent juxtapositions among different structural characteristics that need to be balanced in what we envision as social network structures conducive to adaptive co-management of natural resources. We argue that it is essential to develop an understanding of the effects that different structural characteristics of social networks have on natural resource management.